2012
DOI: 10.1002/adma.201104195
|View full text |Cite
|
Sign up to set email alerts
|

Barrier‐Guided Growth of Micro‐ and Nano‐Structured Graphene

Abstract: A novel approach for the rational synthesis of low-defect density, patterned graphene from the bottom up, called barrier-guided chemical vapor deposition, is introduced. A patterned barrier layer impedes the growth of graphene in selected areas of the copper substrate, guiding the growth of graphene into desired micro- and nano- structures with control over placement, orientation, and spatial and lateral extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 29 publications
5
59
0
Order By: Relevance
“…Very recently, Safron et al reported the fabrication of GNR arrays and GNM via e-beam lithography and block copolymer lithography23. In this work, we show that large-scale graphene nanostructures can be directly grown on patterned copper (Cu) foil, which can be easily transferred for device application, and that the as-grown graphene nanostructures possess much smoother edges compared with etched counterpart, which is confirmed by direct observation with transmission electron microscopy (TEM).…”
supporting
confidence: 67%
“…Very recently, Safron et al reported the fabrication of GNR arrays and GNM via e-beam lithography and block copolymer lithography23. In this work, we show that large-scale graphene nanostructures can be directly grown on patterned copper (Cu) foil, which can be easily transferred for device application, and that the as-grown graphene nanostructures possess much smoother edges compared with etched counterpart, which is confirmed by direct observation with transmission electron microscopy (TEM).…”
supporting
confidence: 67%
“…This method has been effective in dialing in the right interfacial energies between a solid substrate and an overlying block copolymer (BCP) film [2,42,43], leading to perpendicularly oriented periodic microdomain arrays. These domains are useful for nanolithographic applications [44][45][46][47][48][49][50][51]. In a seminal work of Mansky et al, surface-grafted a hydroxyl terminated poly(styrene-random-methyl methacrylate) (P(S-r-MMA)) brush to modify the interfacial energies between the substrate and the blocks of poly(styrene-block-methyl methacrylate) (P(S-b-MMA)) [2,40,42,[52][53][54][55][56] (Figure 2c,d).…”
Section: Solid State Graftingmentioning
confidence: 99%
“…Although this equation does not take into account the entire complex physics occurring in nanostructured graphene, it is still appropriate as it seems to have a reasonable match with experimental data for various NPG structures. [47] While extensive studies have been carried out on the physical properties of SLG, less is known about the electrical properties of FLG structures. We find that the electrical properties in graphene nanoscale transistors are strongly affected by the number of graphene layers, the channel width, and the trapped charge in the SiO 2 substrate, consistent with the findings by Lin and Avouris [48] and Sui and Appenzeller [49].…”
Section: Resultsmentioning
confidence: 99%